Synthesis and Characterisation of Mono- and Bidentate Alkoxybenzimidazolin-2-ylidene Palladium Complexes: Interesting Solution Behaviour and Application in Catalysis - Simpson, P.; Skelton, B.; Brown, David; Baker, M. (Wiley-VCH Verlag GmbH & Co, 2011)
New mono- and bidentate N-heterocyclic carbene (NHC) silver and palladium complexes bearing benzimidazolin-2-ylidene ligands have been synthesized and structurally and spectroscopically characterised. The NHC ligands are decorated with bulky substituents on the nitrogen atoms and electron-donating butoxy groups on the benzo-fused ring, with the aim of enhancing the ability of their complexes as catalysts. The two types of palladium complexes presented, which possess either a bidentate bis(NHC) or a mixed NHC/allyl ligand system, demonstrate significantly different activities in the Mizoroki–Heck cross-coupling reactions but similar activities in the Suzuki–Miyaura and Buchwald–Hartwig reactions. Interesting behaviour of the mixed NHC/allyl palladium complexes in solution has been investigated.